Efektivitas Hukum dalam Penanganan Pelanggaran Hak Asasi Manusia Berat pada Tragedi Semanggi (1998–1999) - Zaharatul Jannah Dwi Putri; Leni Maryani; Sri Fathimah Ramadhani (Progressive Law Review, 2025)
The Semanggi Tragedies I (1998) and II (1999) marked two major episodes of violence during Indonesia’s political transition from the New Order regime to the Reform era. Both incidents resulted in dozens of deaths and hundreds of injuries, thereby falling into the category of alleged gross human rights violations. However, more than two decades later, their handling has shown no significant progress. This study aims to examine the historical context of these events, the position and responsibility of the state in the human rights violations that occurred, and the extent to which the legal response to the Semanggi Tragedies aligns with Soerjono Soekanto’s Theory of Legal Effectiveness. The study employs a normative juridical method with qualitative descriptive analysis. The data used are entirely secondary, including legislation, official parliamentary records, documents from the National Commission on Human Rights (Komnas HAM), civil society reports, academic literature, and relevant media coverage. Data were collected through library research and systematically analyzed to produce deductive conclusions regarding the effectiveness of legal enforcement in the Semanggi cases. The findings show that the handling of the Semanggi cases fails to meet the indicators of legal effectiveness. In terms of regulation, there exists a duality of interpretation regarding investigative authority between Komnas HAM and the Attorney General’s Office. From the perspective of legal apparatuses, inconsistencies persist, including statements from the Attorney General that contradict the mandate of the Human Rights Court Law. Meanwhile, evidentiary infrastructure has weakened due to the lengthy passage of time and the limited availability of forensic evidence. Lastly, public responses reflect a low level of trust in formal human rights enforcement mechanisms. Overall, this study underscores that the handling of the Semanggi Tragedies remains far from effective and requires comprehensive reform to ensure legal certainty and justice for the victims.